Introduction to information flow management (IFC) - Umurzakov O. Sh.; Karshiev Z. A. (Research Parks Publishers, 2021)
Data flow management is very important today. The article discusses security and integrity in data flow management, tags, explicit and implicit flows, and the level of granularity.